Antihyperglycemic Effect of Ceremai Leaf Extract (Phyllanthus acidus) in Mice (Mus musculus) with Diabetes Mellitus Type II - Aminah, Fourth Three Badriyatul; Qomariyah, Nur (LenteraBio : Berkala Ilmiah Biologi, 2023)
Induction of High Fat Diet and alloxan causes increasing free fatty acids that trigger the formation of reactive oxygen species and insulin resistance then the metabolism of blood sugar levels is disrupted. The antioxidant of Phyllanthus acidus leaf extract has the potential to stabilize insulin. This study aimed to determine the effect of P. acidus leaf extract on reducing fasting blood glucose (FBG) and pancreatic histopathology of type II diabetes mellitus (DM) mice. The experimental study used 24 DDY strain male mice, divided into six groups consisting of the control group, negative control (HFD and Alloxan), positive (Metformin), dose I (215 mg/kg BW), dose II ( 230 mg/kg BW), and dose III (245 mg/kg BW). HFD induction was conducted for 8 weeks combined with a single dose of alloxan and 21 days of extract. Data were analyzed with One-way ANOVA, continuing with Duncan's test. The results proved that this extract significantly affected decreasing FBG (p=0.004) and level of pancreatic damage (p=0.008). Based on results, it can be concluded that P. acidus leaf extract has an antihyperglycemic effect on reducing FBG of type II DM mice within normal also being able to trigger pancreatic β cell regeneration compared to other treatments with dose III (245 mg/kg BW) as the optimal extract dose.